A study on free bike sharing for sustainable environment in Melaka Tengah, Malacca / Nurul Shawaltul Aini Zamli and Siti Suraya Mohd - Zamli, Nurul Shawaltul Aini; Mohd, Siti Suraya (Faculty of Administrative Science and Policy Studies, 2012)
This study examines the awareness of benefit gain of free bike sharing in Melaka Tengah. In addition, this study also attempts to determine the differences of customer based on their demographic. Other than that, this study also hypothesized whether there are significant relationships in free bike sharing towards healthy lifestyle reduce pollution and reduce congestion. Questionnaire as been used as a research instruments were used to obtain data. A total of 348 respondents were distributed with questionnaire around Melaka Tengah. The sample of study and data was analyzed by “Statistical Package for Social Science” (SPSS Window) Version 19.0. The tests involved are Reliability Test, Descriptive Analysis, and Spearman Correlation. The results of the awareness of benefit gain of free bike sharing are support the hypothesis. Furthermore, the result also found most of the respondent never heard and familiar with this free bike sharing term. In addition, some suggestions have been recommended for increase the awareness of benefit gain of free bike sharing in Melaka Tengah.